Pediatric formulations in national essential medicines lists: a cross-sectional study - Heredia, Camila; Ul Haq, Moizza Zia; Cappello, Bernadette; Malik, Farihah; Penazzato, Martina; Moja, Lorenzo; Persaud, Navindra (Frontiers in Pediatrics, 2025)
BackgroundChildren need specialized medicine formulations for proper dosing, safety, and adherence. The World Health Organization developed a pediatric essential medicines list prioritising pediatric formulations. Given global commitment by countries to children's health, we expected national lists similarly prioritizing pediatric medicines and formulations. We assessed the extent to which national lists include medicines for children.MethodsWe used a global essential medicines database to collect data on national lists identifying pediatric lists, medicines, and formulations. Six key therapeutic areas were selected a priori to present granular data. Data were categorized by country characteristics and income levels.ResultsOur study found that most countries do not include pediatric formulations in their Essential Medicine Lists (EMLs), especially high-income European countries. Of the 22 countries that do, most list medicines for infections, antiretrovirals, and cancer, but gaps exist for antitrypanosomal, antileishmanial, and antihepatitis treatments. Paracetamol had the most diverse formulations. Additionally, differences were found between national and World Health Organization (WHO) EMLs, with some countries listing fewer medicines overall, though some countries included more treatments for HIV and hepatitis than the WHO Essential Medicines List for children (EMLc).ConclusionIn many countries, it is unclear which medicines for children are prioritized, if any. The problem is particularly acute in high-income countries. Misalignments between national lists and the World Health Organization are common. There is little evidence that countries are adequately implementing medicines policies for youth.